Tunisia : 2000 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Tunisia showed strong economic performance and social achievements owing to its prudent macroeconomic policies. Executive Directors commended this development, and underscored the importance of complementing the trade liberalization with the European Union with comprehensive trade and price liberalization measures, and sustained structural reforms. They appreciated the achievement of price stability, and noted the dual role played by incomes and monetary policies. They welcomed the substantial improvements in the quality and dissemination of statistical information, and the country's subscription to the Special Data Dissemination Standard.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet